1999
DOI: 10.1002/hep.510290348
|View full text |Cite
|
Sign up to set email alerts
|

Liver resection and needle liver biopsy cause hematogenous dissemination of liver cells

Abstract: We have investigated whether liver resection and needle liver biopsy cause dissemination of liver cells into peripheral blood circulation, using a reverse-transcription polymerase chain reaction (RT-PCR)-based assay targeted against ␣-fetoprotein (AFP) mRNA. Twelve patients with and 16 without primary liver cancer (PLC) undergoing liver resection were tested before skin incision, after liver mobilization, after hepatic parenchyma transection, after abdominal wall suture, and 4 days after surgery. Two patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 13 publications
3
53
0
Order By: Relevance
“…However, tumors recur in 20% of them within 2 years (Bismuth et al, 1993;Majno et al, 1997;Poon et al, 2002). HCC tumor cells can infiltrate the BM and the blood system, as shown by the presence of alpha-fetoprotein (AFP) messenger RNA (mRNA) (Matsumura et al, 1994;Lemoine et al, 1997;Louha et al, 1999;Kienle et al, 2000;Gross-Goupil et al, 2003). The number of circulating tumor cells has been related to tumor size (Matsumura et al, 1994;Lemoine et al, 1997;Minata et al, 2001;Gross-Goupil et al, 2003) and to the risk of recurrence (Minata et al, 2001;Qin and Tang, 2002;Gross-Goupil et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tumors recur in 20% of them within 2 years (Bismuth et al, 1993;Majno et al, 1997;Poon et al, 2002). HCC tumor cells can infiltrate the BM and the blood system, as shown by the presence of alpha-fetoprotein (AFP) messenger RNA (mRNA) (Matsumura et al, 1994;Lemoine et al, 1997;Louha et al, 1999;Kienle et al, 2000;Gross-Goupil et al, 2003). The number of circulating tumor cells has been related to tumor size (Matsumura et al, 1994;Lemoine et al, 1997;Minata et al, 2001;Gross-Goupil et al, 2003) and to the risk of recurrence (Minata et al, 2001;Qin and Tang, 2002;Gross-Goupil et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The number of circulating tumor cells has been related to tumor size (Matsumura et al, 1994;Lemoine et al, 1997;Minata et al, 2001;Gross-Goupil et al, 2003) and to the risk of recurrence (Minata et al, 2001;Qin and Tang, 2002;Gross-Goupil et al, 2003). However, the relevance of AFP mRNA as a marker of circulating tumor cells is controversial because these cells have not been further characterized and because we and others have shown that they may correspond to normal circulating hepatocytes (Lemoine et al, 1997;Louha et al, 1999;Minata et al, 2001). Furthermore, these tumor cells have mostly been sought and detected shortly after liver resection (Matsumura et al, 1994;Lemoine et al, 1997;Louha et al, 1999;Kienle et al, 2000;Minata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Ozawa (10) described the anterior transection technique in 1990. This technique was popularized over the next decade (11)(12)(13)(14)(15), driven by the perceived disadvantages of conventional right liver mobilization, namely impaired hepatic blood flow with rotational displacement of the liver (10), potential avulsion of hepatic veins (13), iatrogenic tumour rupture (13,16), and hematogenous dissemination of malignant cells when the hepatic veins remained patent (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Louha found unexpectedly that liver cells began spreading at an early stage during surgery, i.e., after liver mobilization and rotation, before liver parenchyma transection. This was probably related to the sponge-like structure of the liver and to the stretching and compression of the organ during liver mobilization [42] . Surgery-related liver cell spreading also occurred more frequently, compared with that induced by needle liver biopsy.…”
Section: Discussionmentioning
confidence: 99%